Duration of HIV-1 viral suppression on cessation of antiretroviral therapy in primary infection correlates with time on therapy. - Wolfgang Stöhr; Sarah Fidler; Myra McClure; Jonathan Weber; David Cooper; Gita Ramjee; Pontiano Kaleebu; Giuseppe Tambussi; Mauro Schechter; Abdel Babiker; Rodney E Phillips; Kholoud Porter; et al. (PLoS ONE)
Objective A minority of HIV-1 positive individuals treated with antiretroviral therapy (ART) in primary HIV-1 infection (PHI) maintain viral suppression on stopping. Whether this is related to ART duration has not been explored. Design And Methods: Using SPARTAC trial data from individuals recruited within 6 months of seroconversion, we present an observational analysis investigating whether duration of ART was associated with post-treatment viraemic control. Kaplan-Meier estimates, logistic regression and Cox models were used. Results 165 participants reached plasma viral loads (VL) <400 copies/ml at the time of stopping therapy (ART stop). After ART stop, 159 experienced confirmed VL ≥400 copies/ml during median (IQR) follow-up of 167 (108,199) weeks. Most participants experienced VL rebound within 12 weeks from ART stop, however, there was a suggestion of a higher probability of remaining <400 copies/ml for those on ART >12 weeks compared to ≤12 weeks (p=0.061). Cumulative probabilities of remaining <400 copies/ml at 12, 52 and 104 weeks after ART stop were 21% (95%CI=13,30), 4% (1,9), and 4% (1,9) for ≤12 weeks ART, and 32% (22,42), 14% (7,22), and 5% (2,11) for >12 weeks. In multivariable regression, ART for >12 weeks was independently associated with a lower probability of being ≥400 copies/ml within 12 weeks of ART stop (OR=0.11 (95%CI=0.03,0.34), p<0.001)). In Cox models of time to VL ≥400 after 12 weeks, we only found an association with female sex (OR=0.2, p=0.001). Conclusion Longer ART duration in PHI was associated with a higher probability of viral control after ART stop. Trial registration Controlled-Trials.com 76742797 http://www.controlled-trials.com/ISRCTN76742797.